1983
DOI: 10.1007/bf02553341
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hidradenitis suppurativa of the anal canal

Abstract: Obstruction of the outlet of the apocrine duct adjacent to the skin surface, with subsequent rupture into the intradermal plane, initiates the inflammatory condition termed "hidradenitis suppurativa." The chronic manifestations of the process, indicated by recurrent abscess formation, draining sinuses, skin fistulas, and an intense cicatricial response, usually affect the distal two thirds of the anatomic anal canal because the proximal portion is devoid of hair follicles and accessory glands. An anal fistula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Systematic comparison of studies is hampered by variable definitions of recurrence. The deroofing technique, as used in this study, was first described in 1959 by Mullins et al 9 In 1983 Culp 15 reported on deroofing in a group of 30 patients with HS of the anal region. Unfortunately recurrences and follow-up were not studied and the diagnosis of HS was questionable.…”
Section: Discussionmentioning
confidence: 98%
“…Systematic comparison of studies is hampered by variable definitions of recurrence. The deroofing technique, as used in this study, was first described in 1959 by Mullins et al 9 In 1983 Culp 15 reported on deroofing in a group of 30 patients with HS of the anal region. Unfortunately recurrences and follow-up were not studied and the diagnosis of HS was questionable.…”
Section: Discussionmentioning
confidence: 98%
“…2 Patients with anogenital HS may also have disease in the anal canal (30 of 132 patients in one study). 26 HS in the anal canal lies superficial to the internal sphincter and begins in the lower two-thirds of the canal, distal to the dentate line (the transition zone from columnar epithelium to squamous epithelium). 26 This corresponds with the distribution of apocrine glands and hair follicles in the anal canal.…”
mentioning
confidence: 99%
“…26 HS in the anal canal lies superficial to the internal sphincter and begins in the lower two-thirds of the canal, distal to the dentate line (the transition zone from columnar epithelium to squamous epithelium). 26 This corresponds with the distribution of apocrine glands and hair follicles in the anal canal. 26 If lesions are seen proximal to this area, disorders such as Crohn disease (CD) or a fistulous abscess should be considered.…”
mentioning
confidence: 99%
See 2 more Smart Citations